2013
DOI: 10.1111/jgh.12083
|View full text |Cite
|
Sign up to set email alerts
|

The influence of metastatic site on the expression of CEA and cellular localization of β‐catenin in colorectal cancer

Abstract: Our findings indicate that lung microenvironment is unique in that it suppresses the expression of CEA by CRC cells forming neoplastic glands. In addition, lung microenvironment promotes nuclear localization of β-catenin, suggesting that the Wnt signaling pathway is relatively active highly in CRC metastasized to lung, when compared with liver or colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…26 Furthermore, clinical research in patients has discovered significantly increased levels of surface CEA in biopsies of metastasized colorectal can-cer from the liver. 27 These observations, together with our study, suggest the possibility that suppressed T-cell functions caused by CEA may be responsible for tumor metastasis and stabilization. Intriguingly, we also show that the inhibitory effect is limited when CEA proteins are administered in a soluble form.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…26 Furthermore, clinical research in patients has discovered significantly increased levels of surface CEA in biopsies of metastasized colorectal can-cer from the liver. 27 These observations, together with our study, suggest the possibility that suppressed T-cell functions caused by CEA may be responsible for tumor metastasis and stabilization. Intriguingly, we also show that the inhibitory effect is limited when CEA proteins are administered in a soluble form.…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, a recent report has demonstrated the importance of tumor cell CEA surface expression for metastasis showing CEA‐mediated promotion of tumor implantation in mice . Furthermore, clinical research in patients has discovered significantly increased levels of surface CEA in biopsies of metastasized colorectal cancer from the liver . These observations, together with our study, suggest the possibility that suppressed T‐cell functions caused by CEA may be responsible for tumor metastasis and stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…However, specificity (94.59 %) of MRI-detected MVI was significantly higher than that of CEA (67.57 %; p<0.05). Rao et al [26] reported that colorectal cancer neoplastic glands formed in liver expressed high CEA level but CEA expression in the neoplastic glands was considerably lower than in the tumour necrotic regions in the lungs. Villeneuve et al [27] suggested that preoperative CEA level≥10 ng/mL was prognostic factor in patients with lung metastasis from colorectal cancer.…”
Section: Discussionmentioning
confidence: 98%
“…They showed that significantly higher CEA expression in CRC tissues and liver tumor glands than in normal colon crypt tissues, but no difference in CEA expression between CRC primary foci and liver metastases, which all expressed high levels of CEA. 9,18 All the above results were obtained by pathological scoring of cells that stained negatively, weakly, or strongly positive, but ratios of CEA-positive cells were not precisely quantified. As showed by our results, up to ∼80% of cells in paired primary and liver metastasis tissues were CEA-positive (Table 2), but the proportion of CEA-positive cells was significantly higher in liver metastases than in paired primary foci from the same patient (Figures 2B and 4).…”
Section: Discussionmentioning
confidence: 99%
“…7 Levels of CEA expression differ in primary foci of CRC among patients 8 and between CRC primary foci and liver metastases. 9 Studies have analyzed the heterogeneity of CEA in the primary foci of CRC. Compared with the corresponding CEA-positive cells, CEA-negative cells showed higher tumorigenic and metastatic abilities.…”
Section: Introductionmentioning
confidence: 99%